Comprehensive analysis of RNA binding motif protein 3 (RBM3) in non‐small cell lung cancer. (3rd June 2020) - Salomonsson, Annette; Micke, Patrick; Mattsson, Johanna S. M.; La Fleur, Linnea; Isaksson, Johan; Jönsson, Mats; Nodin, Björn; Botling, Johan; Uhlén, Mathias; Jirström, Karin; Staaf, Johan; Planck, Maria; et al.
Abstract: Aims: High expression of the RNA‐binding motif protein 3 (RBM3) correlates with improved prognosis in several major types of cancer. The aim of the present study was to examine the prognostic value of RBM3 protein and mRNA expression in non‐small cell lung cancer (NSCLC). Methods and results: Immunohistochemical expression of RBM3 was evaluated in surgically treated NSCLC from two independent patient populations (n = 213 and n = 306). Staining patterns were correlated with clinicopathological parameters, overall survival (OS), and recurrence‐free interval (RFI). Cases with high nuclear RBM3 protein expression had a prolonged 5‐year OS in both cohorts when analyzing adenocarcinomas separately ( P = .02 and P = .01). RBM3 remained an independent prognostic factor for OS in multivariable analysis of cohort I (HR 0.44, 95% CI 0.21‐0.90) and for RFI in cohort II (HR 0.38, 95% CI 0.22‐0.74). In squamous cell carcinoma, there was instead an insignificant association to poor prognosis. Also, the expression levels of RBM3 mRNA were investigated in 2087 lung adenocarcinomas and 899 squamous cell carcinomas assembled from 13 and 8 public gene expression microarray datasets, respectively. The RBM3 mRNA levels were not clearly associated with patient outcome in either adenocarcinomas or squamous cell carcinomas. Conclusions: The results from this study support that high protein expression of RBM3 is linked to improved outcome in lung adenocarcinoma. Abstract : High protein expression of RBM3 was associated with longer survival time in resected lung adenocarinoma in two independant cohorts. The association to outcome was not seen in squamous cell carcinomas or for mRNA levels.